Hand-foot-clothes contamination innuclear medicine: monitoring of staff at Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) - Sithole, Phumlani (My University, 2021)
Aim: This study seeks to assess contamination due to emitting radionuclides on hands, feet and clothing of staff in the nuclear medicine department. To achieve our aim, we measured the radionuclide contamination level of each staff member and compared the level of contamination among different staff categories (doctors, radiographers, nurses, general workers and students). We also determined the area that contributed to high contamination. Methods: The study was conducted at Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) for three months. We used a hand-foot-clothes contamination monitor (Mod CMS60DXD) to measure the level of radioactive contamination. Twelve doctors, fourteen radiographers, five students, four nurses, one medical physicist, one administrator, one secretary and two cleaners were enrolled in the study. The radioactive contamination was measured on the hands, feet and clothing of each participant. The measurements were taken in the morning, at lunchtime and just before leaving duty after work. Ethical permission for the study was received from the Human Research Ethics Committee (Human) of the University of the Witwatersrand (Clearance Certificate No. M170203). Results: The detected radioactive contamination frequency was within the derived limit for surface contamination in 93% of left hands, 92% of right hands, 92% of left feet, 93% of right feet and 88% of clothing. Radiographers and students were most exposed to contamination outside the allowed limit. Contamination was not significant at the beginning of the day but increased with time and was mainly detected at lunchtime and before leaving work. Hot laboratory and gamma camera imaging rooms had the highest detected contamination. The primary source of contamination was 99mTc radionuclide compared to18F and123I radionuclides. Conclusion: The results indicate that there is radioactive contamination in the Nuclear Medicine Department at CMJAH. Although the measured radioactive contamination was within the derived limit for surface contamination in the vast majority of participants, it remains vital to introduce mechanisms that will minimise staff exposure to radioactive contamination
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, ,in fulfilment of the requirements for the degree of Master of Science, School of Physics